Post traumatic stress disorder among former child soldiers attending a rehabilitative service and primary school education in northern Uganda. - Ovuga, Emilio; Oyok, Thomas O.; Moro, E.B. (African health sciences, 2008)
This study was prompted by the psychiatric hospitalization of 12 former child soldiers of the Lord’s Resistance Army (LRA) at a rehabilitation school in northern Uganda with a case of mass psychotic behavior. Objectives: To report the prevalence of post-traumatic stress disorder, depressed mood, and associated risk factors. Methods: Data on post-traumatic stress disorder, depressed mood, physical disabilities, socio-demographic variables, and the children’s war experiences were collected in face-to-face interviews using the Harvard Trauma Questionnaire (HTQ), a modified Hopkins Symptoms Check-List (HSCL), and a 15-item War Trauma Experience Check-list (WTECL-15). Data was analyzed with SPSS version 11.0. Results: There were 58 girls and 44 boys. Eighty nine children (87.3%) reported having experienced ten or more war-related traumatic psychological events; 55.9% of the children suffered from symptoms of post-traumatic stress disorder, 88.2%, symptoms of depressed mood and 21.6% had various forms of physical disability. Nearly half of the children (42.2%) reported a positive family history of severe mental illness; 10.8%, a family history of suicide; 22.5%, a family history of suicide attempt; and 45.1%, a family history of alcohol abuse. Children who experienced 10 or more traumatic war events were more likely than the rest to experience depressed mood. Return through a reception center or through a cleansing ritual did not protect against depression. Discussion: Post-traumatic stress disorder among former LRA child soldiers at a rehabilitation centre in northern Uganda is presented. The report highlights the huge unmet need for psychological services among former child soldiers of the LRA.
Keywords: Post traumatic stress disorder; Child soldiers; Rehabilitative service; Primary school education; Northern Uganda